Passions, Sympathy and Print Culture
XI, 290 p.
Keywords: This book explores ways in which passions came to be conceived, performed and authenticated in the eighteenth-century marketplace of print. It considers satire and sympathy in various environments, ranging from popular novels and journalism, through philosophical studies of the Scottish Enlightenment, to last words, aesthetics, and plastic surgery.